Pengaruh Media Papan Hitung terhadap Kemampuan Berhitung Anak Usia 5-6 Tahun di TK Aisyiyah 14 Ampang Padang - Muria, Jenni; Rakimahwati, Rakimahwati (Asian Journal of Early Childhood and Elementary Education, 2023)
This study aims to determine how influential the Counting Board Media is on children's counting skills at Aisyiyah 14 Ampang Padang Kindergarten. This study uses a quantitative approach with the Quasy Experiment method. The study population was all children in Aisyiyah 14 Ampang Padang Kindergarten, namely class B1 as the experimental class and class B2 as the control class. The data collection technique used is the form of oral tests and action tests. Then the data was processed with normality test, homogeneity test, and hypothesis testing. Based on data analysis, the normality test obtained data in the experimental class and control class were normally distributed. In the homogeneity test, the data is homogeneous. Then based on the hypothesis test, the sig value (2 tailed) is 0.023 and 0.025, and this value is <0.05. Thus it is concluded that there is a significant influence (real) between learning conducted by researchers in experimental classes with counting board media in learning with those conducted by teachers with number cards to improve children's counting skills at Aisyiyah 14 Ampang Padang Kindergarten.